Cultural Influences on Waste Dump and Separation Behaviors in Future Capital of Indonesia (Study Case in Sepaku Regency, Indonesia) - Dinansyah Wiradimadja, Dafi; Mori, Hisatsuna; Rizkiah, Riza (Technium Education and Humanities, 2023)
Garbage in Indonesia is a serious problem that has an impact on the social, economy and culture of society. Almost all cities in Indonesia experience problems in processing waste, including in the future capital of Indonesia. The research found that many Indonesians have NIMBY syndrome, the throwing garbage anywhere when they are outside their home, when the eating on the street they usually throw their garbage onto the street or into a gutter. In some ethnic groups in Indonesia, littering is also a tradition from their ancestors. In some culture, deliberately make the floor of their houses on stilts rather sparse to make it easier for them to dispose of food waste from inside their homes, likewise, in some community, they throw food waste directly from the kitchen window to the outside of the house. According to observations, this is almost evenly done by older generations at the level of people who born in the 1940s. The current habit of waste if we look again, are the legacy and education from the previous generation where that the garbage they dumped everywhere in the past was partly organic waste, the food and the things they use including bags, cutlery and so on are mostly made from organic materials that come from the environment around them, so that whatever they throw away, if not eaten by pets, will decompose so quickly in the ground. it is even useful for soil, therefore, even though littering activities are carried out, the streets in the village in the past were still clean of garbage. This article meant to seek the cultural background behind NIMBY syndrome in Indonesia. This research used Mixed Methods approach (quantitative and qualitative) and use secondary data review, direct observation and semi semi-structured interviewing to collect the data. This research found that the main factor for the success of this program is the people who willing to be open concerning the program and its concepts, thus becoming aware about their environmental problems, they willing to work for the benefit of their village. In this village the push fac-tor are economic and re-education aspects that move the people to save their environment. The economic benefit from gar-bage bank also have helped this program. The research showed that the respondents who have lower education level have more tendency on separating their waste than the respondents who have higher education level, and the research also showed that the respondents who separating their waste showed have higher income level. The research concluded that here isn’t much evidence of a causal link between education, income level and pro-environmental behavior.